MELAKSANAKAN PERINTAH JABATAN SEBAGAI ALASAN PENGHAPUSAN PIDANA DALAM PERKARA TINDAK PIDANA KORUPSI : Studi Kasus Putusan Mahkamah Agung Nomor : 416 Pk/Pid.Sus/2019 - Grasella Shafiyah Putri (2022)
The criminal act of corruption is a disgraceful act that aims to financially benefit oneself, family or group, which involves state officials. Various arguments were put forward by the Defendant in the case of a criminal act of corruption in order for the judge to make an acquittal. One of the reasons is that the Defendant carried out the position order as stated in Article 51 of the Criminal Code. In the decision Number: 416 Pk/Pid.Sus/2019, the convict received an acquittal by the judge and one of the considerations was that the convict carried out the position order. The lack of uniformity in the size of carrying out this office order is one of the causes of the failure of the prosecution process against the defendant in the corruption case. For this reason, the issues raised are: First, how is the interpretation of the Position Order according to the provisions of Article 51 of the Criminal Code. Second, how is the application of Article 51 of the Criminal Code as the reason for the abolition of the crime in the corruption case. Judicial Review Decision Number: 416 Pk/Pid.Sus/2019 dated January 8, 2020. The method used in this study is a qualitative method, namely using data through library studies such as legislation. -invitations, books, and journals, as well as through case studies in the decision Number: 416 Pk/Pid.Sus/2019. The results of the study conclude, First, Article 51 paragraph (1) of the Criminal Code is the basis for eliminating an act against the law of an act (justification) for carrying out a legal position order. While Article 51 paragraph (2) of the Criminal Code is the basis for eliminating criminal liability to the perpetrator (forgiving reasons), namely in good faith thinking that the order is based on a valid order within its authority. The application of Article 51 of the Criminal Code, especially paragraph (2) in the Judicial Review Decision Number 416 Pk/Pid.Sus/2019 dated January 8, 2020 because the convict in carrying out his actions was based on orders that were within the dimension of public legal authority in good faith carrying out orders from his superiors so that the convict himself there is a forgiving reason, which means that it is against the law, but the convict cannot be sentenced to a sentence because there are things that are the reason for eliminating the guilt.